Electrospun core–shell nanofibers for drug encapsulation and sustained release. Issue 8 (16th January 2013) - Maleki, Mahboubeh; Latifi, Masoud; Amani‐Tehran, Mohammad; Mathur, Sanjay
Abstract Fabrication of core–shell nanofibers by coaxial electrospinning system suited for drug delivery applications was investigated based on tetracycline hydrochloride (TCH) as the core and poly(lactide‐co‐glycolide) as the shell materials. Comparison of drug release from monolithic fibers (blend electrospinning) and core–shell structures was performed to evaluate the efficacy of the core–shell morphology. The nanofibrous webs are potentially interesting for wound healing purposes since they can be maintained for an adequate length of time to gradually disinfect a local area without the need of bandage renewal. Further, our studies showed the potential of core–shell nanostructures for sustained drug release, which also suppressed the burst release effect from 62 to 44% in the first 3 hours by adding only 1 wt% TCH to the polymeric shell. POLYM. ENG. SCI., 2013. © 2013 Society of Plastics Engineers